The Role of Notary in the Making of Fidusian Assets for Consumer Protection - Maulana Abdul Mujib; Aryani Witasari; Sukarmi Sukarmi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to determine the role of the notary in making fiduciary deeds for consumer protection based on the Law of the Republic of Indonesia Number 8 of 1999. The approach method in this research is the normative juridical method. The specification of this research is descriptive analytical. The data in this study are secondary data. These problems are analyzed using legal protection theory. Based on the results of the research, the role of the notary in providing services to the public, especially for making fiduciary deeds, is things that must be done so that no parties are harmed and the deed can provide protection and legal certainty The parties come face to face with the Notary. Based on the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Act No. 30 of 2014 concerning the Position of Notary, making a Notary Deed, must be before a Notary according to the form and procedure stipulated by the Law, and refuse to make a deed, if power of attorney that is contrary to Article 18 paragraph (1) letter h. Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection, which states that the power of attorney is an integral part of the standard agreement prepared by the fiduciary recipient.